Analysis of the Interrelationship of the Technical-Tactical Indicators of the Wrestlers - Erimbetov Bayrambay Karlibaevich (Zien Journals, 2022)
This article examines the interrelationship of technical and tactical indicators of wrestlers. Recommendations for the development of technical and tactical indicators and the introduction of effective innovative approaches have been developed.
Keywords: National; struggle; technique; tactics